Brucellosis - A major differential for juvenile idiopathic arthritis (Indian Journal of Case Reports, 2018)
Brucellosis is a Gram-negative, aerobic zoonotic infection acquired by Brucella species and transmitted from animals to humans through the ingestion of infected food products, direct contact with an infected animal, or inhalation of aerosols. Usually, the disease remains undiagnosed due to lack of awareness and inadequate reporting and is a challenging health problem in tropical countries. We report a case of 16-year-old male presenting to us with chronic inflammatory symmetric polyarthritis misdiagnosed as juvenile idiopathic arthritis but later found to be suffering from brucellosis on reevaluation. Through this case report, we would like to highlight the possibility and advantage of the high degree of suspicion for an infectious etiology responsible for arthritis in the background of autoimmunity and would also like to emphasize on the possibility of Brucella inducing a false-positive response for young patients presenting with arthritis.